Effectiveness of tramadol or topic lidocaine compared to epidural or opioid analgesia on postoperative analgesia in laparoscopic colorectal tumor resection - Spindler-Vesel, Alenka (Radiology and oncology (Ljubljana), 2025)
Chronic postoperative pain is the most common postoperative complication that impairs quality of life. Postoperative pain gradually develops into neuropathic pain. Multimodal analgesia targets multiple points in the pain pathway and influences the mechanisms of pain chronification. Patients and methods. We investigated whether a lidocaine patch at the wound site or an infusion of metamizole and tramadol can reduce opioid consumption during laparoscopic colorectal surgery and whether the results are comparable to those of epidural analgesia. Patients were randomly divided into four groups according to the type of postoperative analgesia. Group 1 consisted of 20 patients who received an infusion of piritramide. Group 2 consisted of 21 patients who received an infusion of metamizole and tramadol. Group 3 consisted of 20 patients who received patient-controlled epidural analgesia. Group 4 consisted of 22 patients who received piritramide together with a 5% lidocaine patch on the wound site. The occurrence of neuropathic pain was also investigated. Results. Piritramide consumption was significantly lowest in group 3 on the day of surgery and on the first and second day after surgery. Group 4 required significantly less piritramide than group 1 on the day of surgery and on the first and second day after surgery. The group with metamizole and tramadol required significantly less piritramide than groups 1 and 4 on the first and second day after surgery. On the day of surgery, this group required the highest amount of piritramide. Conclusions. Weak opioids such as tramadol in combination with non-opioids such as metamizole were as effective as epidural analgesia in terms of postoperative analgesia and opioid consumption. A lidocaine patch in combination with an infusion of piritramide have been able to reduce opioid consumption.
Keywords: colorectal tumor; kolorektalni tumor; laparaskopska kirurgija; laparoscopic surgery; pooperativna analgezija; postoperative analgesia